Analysis of Factors Influencing the Human Development Index on the Island of Kalimantan - Jumria Laela Nurhasanah; Abd. Rahim; Basri Bado; Muhammad Syafri; Retno Dwi Hastuti (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2026)
This study aims to analyze the factors influencing the Human Development Index (HDI) in five provinces on the island of Kalimantan during the period 2017–2024. The independent variables used include the number of educators, the number of health workers, the poverty rate, and the unemployment rate. Panel data regression analysis with the Fixed Effect Model (FEM) was used. The results show that the number of educators and the number of health workers have a positive and significant effect on the HDI, while the poverty rate and unemployment rate have a negative and significant effect on the HDI.